(untitled) (Revista Electrónica REDINE, 2018)
The boom reached today by the technologies of information and communication technologies (ICT) and the Internet in particular has generated a change in the role played by people and institutions worldwide, especially in education. Hence, this study was aimed at the creative use of these technologies in the Moodle virtual platform for participants Diploma tutor training obtain the skills to build and validate measurement instruments. A field study, was conducted descriptive. The results suggest the need to design an online course, depending on the academic profile of the students to whom it is addressed. It was concluded that the use and integration of ICT to support classroom teaching to facilitate self- learning, the promotion and development of creativity in both students and teachers is necessary.